Efficient and highly selective boron-doped carbon materials-catalyzed reduction of nitroarenes1. Issue 66 (25th August 2015) - Lin, Yangming; Wu, Shuchang; Shi, Wen; Zhang, Bingsen; Wang, Jia; Kim, Yoong Ahm; Endo, Morinobu; Su, Dang Sheng
<x xml:space="preserve">Abstract</x> Boron-doped carbon materials are demonstrated to be excellent catalysts in nitroarene reduction reactions.